Storynomic Tourism Strategy of Kebo Ketan Ceremonial Art as a Form of Marketing Communication for Eco-Tourism : Storynomic Tourism Strategy of Kebo Ketan Ceremonial Art as a Form of Marketing Communication for Eco-Tourism - Parani, Rizaldi; Hubner, Ira Brunchilda; Juliana, Juliana; Purba, Herman (ETTISAL : Journal of Communication, 2023)
Kebo Ketan celebration held in Sekaralas village, Ngawi by Kraton Ngiyom non-governmental organization (NGO). The myth contained in this ceremonial art is a narrative related to concern for the culture, ecology and economy of the Sekaralas village community. This ceremonial art presenting a giant statue of a water buffalo and symbolic objects such as sticky rice, brown sugar, and musical instruments as well as sacred dances. The aim of this ceremonial art is to convey messages related to preserving the natural environment around the Sekaralas village area, and encouraging increased social cohesiveness of village residents. This research intends to describe and analyze how the storynomic tourism strategy is used through the Kebo Ketan ceremonial art as a form of marketing communication for eco-tourism in Sekaralas village, which can depict the power of culture through myths and rituals, packaged in a narrative form to attract tourists. This research used qualitative approach, with the ethnographic method. Primary data were collected through semi-structured interviews with five informants and also complemented by observation results. The research results show that storynomics has the potential to encourage eco-tourism in Sekaralas village, which can be done mainly through the use of digital media. However, the village residents have not fully understood the meaning of the messages conveyed through the Kebo Ketan ceremonial art, especially regarding environmental conservation and the encouragement to develop the village.